Sikap Berdiri Lama Dalam Menimbulkan Nyeri Punggung Bawah - Hartanto Hartanto; Budiman Hartono; Ken Millen Nathawira (Jurnal MedScientiae, 2022)
A person's attitude in the work environment, such as sitting, squatting and standing, is often associated with the appearance of low back pain (LBP), but prolonged standing have not been widely discussed in Indonesian journal media. This literature study conducted a search for research articles in the PubMed and Google Scholar journal databases. There were 6 journals which stated that prolonged standing was significantly related to LBP, but 2 other journals stated otherwise. Prolonged standing that exceed 20 minutes can put stress on the posterior muscles of the body and the joints of the vertebral column, especially in the lumbar region which can cause LBP with varying levels and quality of pain. The existence of work factors such as workload, length of work, work attitude, tool assistance, and the number of hours of rest, as well as personal factors, such as age, smoking, gender and BMI, can also influence the appearance of LBP in a person, so that someone who has a longer tenure is at greater risk of experiencing LBP than someone who has a new tenure. These factors can potentially bias research results if they are not carefully prepared.